Identification of africanized honey bee (Hymenoptera: apidae) mitochondrial DNA: validation of a rapid polymerase chain reaction-based assay - Pinto, M. Alice (2010)
Polymerase chain reaction (PCR)-ampliÞed mitochondrialDNA(mtDNA)assays have been used in studies of the Africanization process in neotropical feral and managed honey bee populations. The approach has been adopted, in conjunction with morphometric analysis, to identify Africanized bees for regulatory purposes in the United States such as in California. In this study, 211 Old World colonies, representing all known introduced subspecies in the United States, and 451 colonies from non-Africanized areas of the southern United States were screened to validate a rapid PCR-based assay for identiÞcation of Africanized honey bee mtDNA. This PCR-based assay requires a single enzyme digestion (BglII) of a single PCR-ampliÞed segment of the cytochrome b gene. The BglII polymorphism discriminates the mitochondrial haplotype (mitotype) of Apis mellifera scutellata L. (ancestor of Africanized bees) from that of A. m. mellifera, A. m. caucasia, A. m. ligustica, A. m. carnica, A. m. lamarcki, A. m. cypria, A. m. syriaca, and some A. m. iberiensis, but not from that of A. m. intermissa and some A. m. iberiensis. Nonetheless, given the very low frequency ( 1%) of African non-A. m. scutellata mitotype present before arrival of Africanized bees in the United States, cytochrome b/BglII assay can be used to identify maternally Africanized bees with a high degree of reliability.